Lecture listening comprehension through Metacognitive Strategy Instruction (MetSI) / Suzanah Selamat - Selamat, Suzanah (2019)
The main purpose of this mixed-method study was to investigate the effects of metacognitive strategy instruction in enhancing learners’ lecture listening comprehension. Throughout one semester, participants were instructed on the use of several learning strategies which were aimed at helping them understand their lectures more effectively. These learning strategies were chosen as they activate students’ metacognitive skills. Mixed-method data gathering tools were used in the study. A one group pre test post test was conducted to identify participants’ improvement in their lecture comprehension. Participants’ reflective learning journals, semi-structured interviews as well as pre and post questionnaires were also employed to find out their perceptions in using metacognitive strategies to help them cope in their lecture listening. The sample consists of three main groups of participants: (1) an intact class of 34 first year university students, (2) a metacognitive strategy training instructor and (3) a focus group that comprises 6 students from the intact class. The pre test and posttest results were analysed using paired sample t-test while the pre and post questionnaires were analysed using frequency counts and percentages. Results of the pre and post tests indicate a significant increase in the participants’ scores after the MetSI treatment. The results from the MALL questionnaire show an increase level of metacognitive awareness among participants after the treatment. The semi-structured interviews and learning journals elicited positive responses from participants who had used the metacognitive strategies to monitor their lecture comprehension. The results imply that explicit instruction of metacognitive strategies is able to assist lecturers in providing learners with an instrument to monitor their lecture listening comprehension.